Absentee Land Ownership: Problem or Solution for Indonesia Farmers - perkasa, surya rimba; Koeswahyono, Imam; Masykur, Mohammad Hamidi (Universitas Muhammadiyah Malang, 2024)
Food Resilience is a critical aspect of national sustainability programs. Indonesia has a large and diverse population necessitates prioritizing food resilience as a primary focus of government programs. Food security can be achieved by empowering the predominantly farming population of Indonesia. In this regard, the government can utilize Absentee Land to achieve food resilience goals and improve the welfare of farmers. However, the utilization of Absentee Land is hindered by regulations restricting land ownership to civil servants. These regulations pose a significant obstacle to farmers who seek to engage in or expand agricultural endeavors. The conflicts arising from these regulations constitute the most substantial barrier to farmers' efforts to realize food resilience programs in Indonesia. This research uses a normative legal research method, focusing on the Absentee Land through statutory and case approaches. The results of this research indicate that regulations regarding Absentee Land has no longer relevant given the current state of affairs, as they impede the maximization of food resilience, particularly for farmers in the agricultural sector. Abstrak Ketahanan pangan merupakan hal yang sangat penting dalam program keberlangsungan bangsa. Populasi besar dan sangat beragam yang ada di Indonesia menjadikan ketahanan pangan ini harus menjadi prioritas utama dalam program pemerintah. Ketahanan pangan ini dapat diterapkan dengan cara memberdayakan masyarakat Indonesia yang kebanyakan berprofesi sebagai petani. Dalam hal ini pemerintah bisa memanfaatkan Tanah Absentee dalam mencapai tujuan ketahanan pangan dan dapat mensejahterakan petani. Namun dalam pemanfaatan tanah Absentee ini masih terhalang oleh peraturan yang menghambat kepemilikan tanah Absentee untuk para petani. Adanya peraturan tentang kepemilikan tanah Absentee yang hanya dapat dimiliki oleh Pegawai Negeri Sipil menjadi halangan bagi petani yang akan menjalankan atau mengembangkan usaha dalam pertanian. Konflik dalam peraturan kepemilikan tanah Absentee ini adalah hambatan terbesar dalam usaha petani mewujudkan program ketahanan pangan di Indonesia. Penelitian ini akan menggunakan peneltian hukum normatif, dimana dalam studi ini akan menggali penelitian dari tanah Absentee dengan menggunakan pendekatan Perundang-undangan dan pendekatan kasus. Hasil dari penelitian ini bahwa peraturan yang mengatur tentang tanah Absentee ini sudah tidak relevan diterapkan dengan keadaan saat ini karena ketahanan pangan sektor pertanian khususnya bagi petani tidak dapat dimaksimalkan.